Educational support services to school integration and its evolution towards inclusive education. The example of the province of Valladolid - Romero Ureña, Carmen (Avances en Supervisión Educativa, 2014)
The article recounts the evolution and contributions of support services to students with special educational needs created in the province of Valladolid as a result of school integration program. Part of the historical moment of the birth of them that gave them the property of innovators and pioneers and gave them the opportunity to go by themselves to give the answer that the educational community demanded. It analyzes the change to be operating in themselves and the need to approach them in an appropriate manner, at the current time that inclusive education has taken a step that requires rethinking the structure, organization and planning of them.
Keywords: support services; school integration; inclusive education; orientation; early intervention; disability